Giants of the Ocean : Cambridge Reading Adventure : Gold Band - Catherine Bowley (Cambridge, United Kingdom CAMBRIDGE UNIVERSITY PRESS, 2016)
Cambridge Reading Adventures is an international Primary reading scheme which couples an exciting range of texts with precise book-banding from the Institute of Education. Whales are amazing and wonderful creatures. There are many different kinds of whale. This book tells you all about them. A portion of the proceeds of this book will go to the ORCA Charity. ORCA is a UK whale and dolphin conservation charity dedicated to the long term protection of whales, dolphins and porpoises and their habitats. ORCA's projects reach people of all ages providing memorable educational activities and local wildlife experiences both on and off shore. Charity no: 1141728.
Grade 2
Keywords: Leveled reader - Grade 2 -- Leveled reader - Grade 2